More on the Mesopotamian-Yungas disjunction in subtropical and temperate Argentina: Bioclimatic distribution models of the harvestman Discocyrtus dilatatus (Opiliones, Gonyleptidae) - Vergara Oficialdegui, Julia (2015)
In this paper, the potential distribution of the Mesopotamian harvestman Discocyrtus dilatatus Sørensen, 1884 (Opiliones, Gonyleptidae) is modeled, and the species bioclimatic profile is described. Models were built with the presence-only methods MAXENT and BIOCLIM, using 85 unique records (of which 49 are new) and 11 non correlated bioclimatic variables as predictors. Both MAXENT and BIOCLIM supported the Mesopotamian-Yungas disjunct pattern observed in D. dilatatus, as well as confirmed the role of the sub-xeric Dry Chaco as an effective barrier for the two portions of the range. Like in other Mesopotamian harvestmen, temperature variables proved more relevant than precipitation ones in the final models. In the combined overall score obtained with MAXENT, bc4-temperature seasonality ranked as the most relevant, and only one precipitation variable (bc18- precipitation of warmest quarter, in second place) ranked among the top five. In the Most Limiting Factor analysis, which identifies the relevant variables in a local scale, temperature variables demonstrated again being more determining than precipitation ones on most of the range. One single variable, bc5-maximal temperature of warmest month proved critical on the boundaries of the modeled range and the Dry Chaco, suggesting that extremely high temperatures (and not the supposed aridity) are responsible for the 450 km distribution gap.